A Framework for Systematic Design and Construction of an Unmanned Small-scale Air-Land-Water Vehicle - Arhami, Arhami; Hasnan, Khalid; Ab. Wahab, Abas (Journal of Science and Technology, 2010)
In this paper, we present a framework for systematic design and construction of an unmanned small-scale air-land-water vehicle. The systematic design procedure includes design and integration, hardware component selection, as well as experimental evaluation are used to construct a fully functional unmanned small-scale air-land-water vehicle, namely Unmanned Small-scale Air-Land-Water Vehicle (USALWaV). Various component to support maneuver on the ground, flight, and cruising on surface of water feature has been constructed to verify the feasibility and reliability of USALWaV. Double blade axial rotor, propeller set, and pontoon propel the vehicle while fly on-air, move on-land, and float on-water. A control algorithm has also been proposed to allow the USALWaV to travel from its current location to another location specified with changeable channel on Tx Modulator. The results can be followed and used for build a small-scale air-land-water vehicle for research and development purposes.